EFFECT OF METAL ION Cu (II) and Mg (II) ON THE ACTIVITIES ANTIOXIDANT ANTHOCYANIN OF EXTRACT ETHANOL SKIN DRAGON FRUIT RED(Hylocereuspolyrhizus) - Asrul Sani; Ahyar Ahmad; Firdaus Zenta (Hasanuddin University, 2018)
The effect of Cu2+ and Mg2+ metal ions on the antioxidant activity of anthocyanins of ethanol extract from the red dragon skin fruit (Hylocereus polyrhizus) has been done. Anthocyanin pigments from ethanol extract the red dragon skin fruit, content and antioxidant activity of anthocyanins from the red dragon fruit skin with ethanol solvent, and the effect of Cu2+ and Mg2+ metal ions on the antioxidant activity of anthocyanins. Identification of anthocyanin was done by identification of color test, using spectrophotometer analysis of UV-Vis and FTIR. The anthocyanin content was determined using pH difference method, and determined effect of metal ions extract was done by adding 50 ppm, 100 ppm, and 150 ppm of metal ions Cu2+ and Mg2+ into the anthocyanin extract that was been acidified by HCl , using spectrophotometer analysis of FTIR. Antioxidant activity test using DPPH method. The results show that ethanol extracts the red dragon anthocyanin by content is 12.5241 mg / L and antioxidant activity (IC50) is 0.478 μg / mL and with addition of2+ and Mg2+ metal ions can be increased antioxidant activity (IC50) of anthocyanins to be 0.2259 μg / mL for Cu2+ at concentration 50 ppm and 0.3351 μg / mL for Mg2+ at concentration 50 ppm.